2023
DOI: 10.1101/2023.11.27.568924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reversal of pulmonary veno-occlusive disease phenotypes by inhibition of the integrated stress response

Amit Prabhakar,
Rahul Kumar,
Meetu Wadhwa
et al.

Abstract: Pulmonary veno-occlusive disease (PVOD) is a rare form of pulmonary hypertension arising from EIF2AK4 gene mutations or mitomycin C (MMC) administration. The lack of effective PVOD therapies is compounded by a limited understanding of the mechanisms driving the vascular remodeling in PVOD. We show that the administration of MMC in rats mediates the activation of protein kinase R (PKR) and the integrated stress response (ISR), which lead to the release of the endothelial adhesion molecule VE-Cadherin in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Pharmacologically, the administration of chemotherapeutic agents, such as mitomycin C (MMC), bleomycin, and cisplatin, has been implicated in the onset of PVOD (5)(6)(7). Specifically, MMC administration to rats induces a spectrum of PVOD-like phenotypes, including right ventricular (RV) hypertrophy and changes in the pulmonary vasculature, including medial thickening and obstruction of the lumen in PAs and PVs, fibrous growth in the intima and adventitia, and thrombosis (6,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pharmacologically, the administration of chemotherapeutic agents, such as mitomycin C (MMC), bleomycin, and cisplatin, has been implicated in the onset of PVOD (5)(6)(7). Specifically, MMC administration to rats induces a spectrum of PVOD-like phenotypes, including right ventricular (RV) hypertrophy and changes in the pulmonary vasculature, including medial thickening and obstruction of the lumen in PAs and PVs, fibrous growth in the intima and adventitia, and thrombosis (6,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…VE-Cad is a critical component of the adherens junctions (AJs) in endothelial cells, playing an essential role in maintaining permeability and vascular integrity (12). Previous studies have demonstrated that VE-Cad localizes at the AJs in complex with Rad51 (hereafter referred to as VE-Cad:Rad51 complex or VRC) (11). The interaction between Rad51 and VE-Cad is essential for the stability of VE-Cad, as well as for preserving the integrity of endothelial cell-cell junctions and barrier function (11).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations